An impedance tunable and highly efficient triboelectric nanogenerator for large-scale, ultra-sensitive pressure sensing applications. (July 2018) - Rasel, M. Salauddin; Maharjan, Pukar; Salauddin, Md.; Rahman, M. Toyabur; Cho, Hyun Ok; Kim, Jae Woo; Park, Jae Yeong
Abstract: Precise triboelectric nanogenerators (TENGs) with large-scale pressure sensing ability can be realized by effectively harvesting physical pressure. Extensive research on efficient pressure sensors is ongoing, yet the pressure detection limit and sensitivity of most of the reported pressure sensors are not satisfactory for practical and wearable device applications. Herein, we demonstrate a highly efficient approach toward detecting a wide range of pressures, from 5 kPa to 450 kPa, with a record high sensitivity of 0.51 V/kPa. We aim at maximizing the energy conversion efficiency of 48.17% by optimally tuning the internal impedance of the triboelectric nanogenerator at 2.5 MΩ, because low internal impedance results in high output power. This paper reports the structural design, fabrication, and experimental validation of a self-powered and highly durable TENG pressure sensor for large-scale pressure detection based on double-side tribological layers of micro-patterned polydimethylsiloxane (PDMS) and PDMS-multiwall carbon nanotube (CNT) nanocomposites. An in-sole application of the proposed TENG is demonstrated for varying foot pressures corresponding to different walking patterns, which is likely to be applicable in sports sciences, high-risk diabetic foot ulceration, and rehabilitation. Our present contribution not only facilitates large-scale pressure sensing but also paves the way toward the realization of next-generation self-powered and maintenance-free sensing devices. Graphical abstract: fx1 Highlights: A self-powered triboelectric nanogenerator with record high pressure detection range (From 5 kPa to 450 kPa). A maximum of 0.51 V/kPa sensitivity. Up to 48.17% energy conversion efficiency. Low internal impedance of 2.5 MΩ. In-sole application.